Teplizumab: a promising intervention for delaying type 1 diabetes progression - Saleem, Muhammad Rizwan; Khan, Muhammad Talha (Frontiers in Endocrinology, 2025)
Type 1 diabetes (T1D) arises from an autoimmune attack on pancreatic beta cells, leading to a reliance on external insulin to maintain glucose levels. In recent years, research has increasingly focused on preventive strategies for individuals at high risk. A promising new intervention in this field is Teplizumab, the first approved disease-modifying therapy for T1D. Teplizumab is designed to delay progression to stage 3 T1D in adults and children aged 8 years and older who are diagnosed with stage 2 T1D.